Effect of mixed micelles on relative counterion binding constants and counterion-induced micellar growth / Fagge Ibrahim Isah - Fagge, Ibrahim Isah (2017)
Semi empirical kinetic technique has been used to determine the values of both cationic CTABr (hexadecyltrimethylammonium bromide) and mixed cationic-nonionic CTABr-C16E20 (hexadecyltrimethylammonium bromide-polyethoxy hexadecyl ether) micellar relative binding constants (KX/KBr and mKX/mKBr) of counterions, X and Br, (= KXBror RXBr and mKXBr or mRXBr), where superscript “m” signifies mixed micellar system, for X = 2-NaOC6H4CO2, 3,5-Cl2C6H3CO2 and 4-ClC6H4CO2 and correlate them to their specific rheological observations. The kinetic investigations on the influence of CTABr-C16E20 on the values of KXBror RXBr in aqueous solutions of 2-NaOC6H4CO2Na and NaBr has been carried out. The presence of 0.006 M C16E20 decreases the mean values of KXBr or RXBr from 42 to 16 (2.6-fold lower). Rheological measurements of 0.015 M CTABr/2-NaOC6H4CO2Na/H2O solutions at 25 and 35 C revealed a single maximum for [2-NaOC6H4CO2Na] = 0.02 M as the zero shear viscosity (o) was plotted against [2-NaOC6H4CO2Na]. This shows, indirectly, that the is a possibility of the presence of wormlike micelles whereas the possible existence of spherical micelles was revealed at [C16E20]  0.006 M. A similar study, with a different counterion, 3,5-Cl2C6H3CO2 has also been reported. The average value of KXBr or RXBr, for CTABr/3,5-Cl2C6H3CO2Na/H2O solution (KXBr or RXBr = 198) appeared to be almost 2½-fold larger than that of CTABr/3,5-Cl2C6H3CO2Na/C16E20/H2O (mKXBr or mRXBr = 78). Rheometric results of 0.015 M CTABr/3,5-Cl2C6H3CO2Na/H2O solution at 25 and 35 C indicate that the plot of zero shear viscosity (o) against [3,5-Cl2C6H3CO2Na] has two maxima at two different concentrations of 3,5-Cl2C6H3CO2Na (0.015 and 0.04 M) and this also shows the possible existence of wormlike micelles. Contrarily, a possible formation of spherical micelles for CTABr/3,5-Cl2C6H3CO2Na/C16E20/H2O solution ([CTABr]T = 0.015 M and [C16E20]T = 0.006 M) was observed at the same temperatures. The effects of CTABr-C16E20 on 4-ClC6H4CO2 has also been investigated. The respective mean values of KXBr or RXBr obtained for CTABr/4-ClC6H4CO2Na/H2O solution (KXBr or RXBr = 50) is 2.3-fold larger than that of CTABr/4-ClC6H4CO2Na/C16E20/H2O (mKXBr or mRXBr = 22). The possible existence of wormlike micelles was also observed from the rheometric data of 0.015 M CTABr/4-ClC6H4CO2Na/H2O solution based on the plot of o against [4-ClC6H4CO2Na]. The observation also revealed the presence of a single maximum at [4-ClC6H4CO2Na] = 0.03 M where it was thought that spherical micelles were formed in CTABr/4-ClC6H4CO2Na/C16E20H2O with 0.015 M CTABr and 0.006 M C16E20. The quantitative correlation between the magnitudes of relative counterion (X) binding constant (KXBror RXBr and mKXBr or mRXBr) and X-induced cationic micellar structural growth have been reported for the first time in this thesis. The highlight on the possible cause was that adding nonionic surfactant to an aqueous solution of cationic micelle-forming surfactant could be a technique to achieving changes in the structural, as well as the viscoelastic behavior of cationic micelles in the presence of certain inert organic salts.